Integrated Inertial Navigation with Positioning System for Increasing Orbital Module Navigation Accuracy - Mahdi Jafari; Arash Sangary; Jafar Roshanyan (فصلنامه علوم و فناوری فضایی, 2012)
The Inertial navigation system is an ideal solution for motion detection with high accuracy with fast dynamics, but the precise location and status of the system output can be significantly reduced over time. On the other hand, global positioning system is able to determine its position with an average accuracy around the earth. But the GPS alone isn’t enough for navigation of orbital modules, because it doesn’t have situation of orbital modules. The integrated inertial navigation system with global positioning system is a low cost method of providing an accurate and reliable navigation system in the civilian and military aerospace applications. In this paper, using the extended Kalman filter, we design an algorithm to estimate error of sensors, navigation and GPS. This method can be widely used in the integrated navigation INS / GPS in aerospace applications and provides an accurate navigation.